2019
DOI: 10.1136/archdischild-2019-317011
|View full text |Cite
|
Sign up to set email alerts
|

Serious games, a game changer in teaching neonatal resuscitation? A review

Abstract: BackgroundNeonatal healthcare professionals require frequent simulation-based education (SBE) to improve their cognitive, psychomotor and communication skills during neonatal resuscitation. However, current SBE approaches are resource-intensive and not routinely offered in all healthcare facilities. Serious games (board and computer based) may be effective and more accessible alternatives.ObjectiveTo review the current literature about serious games, and how these games might improve knowledge retention and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 47 publications
0
68
0
11
Order By: Relevance
“…Using a methodological approach consisting of: purposeful design, quality evaluation, and dissemination of findings, contributes to the growing body of evidence of serious games as a credible training approach for improving educational outcomes in HCPs and eventual clinical outcomes for patients [22]. While other serious games have been developed for neonatology [11], RETAIN represents a unique simulation-based serious game for neonatal resuscitation training, as is well-described in the research literature [13,14,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a methodological approach consisting of: purposeful design, quality evaluation, and dissemination of findings, contributes to the growing body of evidence of serious games as a credible training approach for improving educational outcomes in HCPs and eventual clinical outcomes for patients [22]. While other serious games have been developed for neonatology [11], RETAIN represents a unique simulation-based serious game for neonatal resuscitation training, as is well-described in the research literature [13,14,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…), and infrastructure (i.e., emotional design to induce stress, competitive points system to rank players' performance, etc.) [11,18]. Moreover, as players receive live feedback about the simulated infant's health in response to the actions taken, RETAIN creates an immersive and emotional environment to generate players interest in the realistic training scenarios [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies show that gamebased learning has achieved good results in the training of dentists and physicians [7,12,13] with every type of game (board games, screen-based games, video games, etc. ), leading to an increase in knowledge [14]. As in this study, similar experiments have shown an increase in knowledge in the short term after the intervention; the long-term anchoring of knowledge has not yet been investigated by us [8].…”
Section: Discussionmentioning
confidence: 49%
“…More than 20 years ago, he recognised that game-based learning in a quiz-style show, such as "Jeopardy", produced an increase in knowledge [5]. There also exist a growing number of papers on this setting reporting mostly positive results [1,3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], research investigating differences between traditional lectures and GBL [6,7,9,14,15], however no one examined "active" players and "passive" listeners.…”
Section: Introductionmentioning
confidence: 99%